2014
DOI: 10.1088/0004-637x/790/2/122
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Age Globular Clusters in Four Galaxy Merger Remnants

Abstract: We present the results of combining Hubble Space Telescope optical photometry with ground-based K s -band photometry from the Gemini imagers NIRI and FLAMINGOS-I to study the globular cluster (GC) populations in four early-type galaxies that are candidate remnants of recent mergers (NGC 1700, NGC 2865, NGC 4382, and NGC 7727). These galaxies were chosen based on their blue colors and fine structure, such as shells and ripples that are indicative of past interactions. We fit the combined VI K s GC data with sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
1
24
2
Order By: Relevance
“…Several observational studies also support this formation scenario (e.g. Whitmore et al 1993;Sikkema et al 2006;Trancho et al 2014).…”
Section: Introductionmentioning
confidence: 75%
“…Several observational studies also support this formation scenario (e.g. Whitmore et al 1993;Sikkema et al 2006;Trancho et al 2014).…”
Section: Introductionmentioning
confidence: 75%
“…The galaxy with the highest L X (gas)/SFR in our sample, NGC 1700, does not appear in Figure 16, due to the lack of FUV data. However, based on optical photometry, the stellar population age in NGC 1700 is estimated to be 1 − 2 Gyrs (Trancho et al 2014) or ∼3 Gyrs (Brown et al 2000).…”
Section: X (Gas)/sfr Vs Stellar Population Agementioning
confidence: 99%
“…Arp 222 has a very low FIR luminosity (10 8.71 L ⊙ ) relative to its K band luminosity (10 11.12 L ⊙ ), thus it is now a relatively quiescent galaxy. However, high resolution optical and IR images revealed the presence of intermediate-age (1 − 2 Gyr) globular clusters in Arp 222 (Trancho et al 2014), suggesting a starburst in the past.…”
Section: 78±mentioning
confidence: 99%
See 1 more Smart Citation
“…It presents a remarkably steep age gradient from a central ∼1.5 Gyr (Sánchez-Blázquez et al 2007;Reda et al 2007) to ∼10 Gyr close to 1R e ; it also has a steep metallicity gradient (Reda et al 2007). Its GCS was studied by Sikkema et al (2006) using HST/ACS, finding a sizeable blue population consistent with a young-to-intermediate GC population (see also Trancho et al 2014). -NGC 3962 is part of the sample of Smith et al (2004) of field ellipticals without companions, as confirmed by Madore et al (2004), and no signs of any tidal disturbance (Tal et al 2009).…”
Section: Galaxy Samplementioning
confidence: 99%